Pengembangan Kecerdasan Spiritual Anak Melalui Lagu-lagu Islami - Romadatul Fitriyah; Bastami Bastami (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
An educator has an important role in guiding and following children, they are required to be able and willing to provide various stimuli in accordance with the potential intelligence of the child. One form of stimulation of Halimah Kindergarten students is taught various forms and types of Islamic nuances known as pats and songs. The songs and claps that are taught include the songs of the names of angels, the pillars of Islam, the pillars of faith and the songs of prayer and so on. By using Islamic songs in the learning process students will be more motivated, faster in learning the material and organize them compared to using conventional methods. Based on the context, the researcher focuses on